Design of Torque Control Strategy for Hybrid Electric Vehicle (HEV) with Maximum Work of Self Commutation Brushless DC Motor using Fuzzy-PI - Hais, Yosi Riduas; Rameli, Mochammad; Effendie, Rusdhianto (Institut Teknologi Sepuluh Nopember, 2018)
Hybrid Electric Vehicle (HEV) is vehicle with least two energy sources, such as Internal Combustion Engine (ICE) and Brushless DC Motor (BLDCM). BLDCM provide additional torque, to purpose of HEV can reach the set point speed according to the reference model. Commutation of BLDCM still complicated, because between the rotational speed of the motor and the speed of the rotary field on the stator should be kept synchronized. Self Commutation used to maintain synchronization between rotation of the rotor and rotary field velocity on BLDCM stator. In addition, this research also applies torque control strategy by using fuzzy-PI controller. Vehicle performance still follows the reference curve with steady state error of 0.1506 km/h and RMSE relative response speed HEV <2%